Pathophysiology and Clinical Outcomes of Vaginal and Cesarean Delivery - Sanatullayevna, Urmanbekova Dilfuza; Omonjon qizi, Zokirjonova Ozoda; Baxtiyorovna, Elmurotova Dilnoza (American Journal of Bioscience and Clinical Integrity, 2026)
The study analyzes ultrasound examinations performed before delivery. An attempt at vaginal delivery was made with a uterine scar following a transverse incision, confirmed by ultrasound. The delivery took place in a fully equipped operating room with continuous monitoring of fetal function and uterine contractions.